Enhancing evaluation practices for Islamic inheritance calculation systems: toward a standardized benchmark - Reda Kurdi, Ghader; Mohammad Justanieah, Hala (Institute of Advanced Engineering and Science, 2025)
Accurate estate distribution is a critical aspect in Islamic law, governed by complex rules that require precise inheritance calculations. Although numerous computerized inheritance calculation systems have been developed, their reliability remains questionable due to inadequate evaluation and unclear criteria for test case selection. This study addresses this gap by introducing a structured evaluation methodology to rigorously assess the functionalities of inheritance calculation systems. A new benchmark comprising 50 test cases was developed by reviewing the functionality of existing systems, collecting prior test cases and identifying coverage gaps through a detailed gap analysis. These benchmark cases were then used to assess the performance of leading online inheritance calculators, comparing their results to expert-validated solutions. Results revealed a significant drop in performance for calculators previously reported to achieve near-perfect accuracy, with scores declining to 68% and 58% compared to earlier reports of 100% and 90%. This demonstrates the effectiveness of the proposed test cases in exposing limitations within current systems. In contrast, the Almwareeth calculator, which had not been previously evaluated, demonstrated the highest accuracy (86%) and was able to handle a wider range of cases. This study lays a critical foundation for advancing the evaluation standards of Islamic inheritance calculation systems, thereby enhancing their reliability in real-world applications.